A study of air molecular contamination (AMC) and volatile organic compounds (VOC) in new AMC/VOC controlled cleanroom - Wong, Chee Kong (Nanyang Technological University, 2020)
Airborne Molecular Contaminants (AMC) may cause different flaws on an electronic device [1]. It is especially so in the semiconductor manufacturing sector. Monitoring of AMC is becoming essential when it comes to managing cleanroom for the present production of semiconductor devices as it advances into DUV and EUV range of manufacturing processes. For this requirement, a new ISO 5 (Class 100) AMC/VOC controlled cleanroom was built with the stringent controlled condition of VOCs of RT>RT toluene, siloxanes and TVOC which is essential to the new advance products to be manufactured in the company premise.